A Comparative Study of Data Management Systems - A. Mostafa, Salama; AbuSalim, Samah Waleed; Saringat, Mohd Zainuri (Journal of Soft Computing and Data Mining, 2020)
Databases play an important role in all areas that use computers such as industry, agriculture, trade, engineering, medicine, etc. Where relevant data is stored in a database. Information systems programmers have long been building their programs on data files and files have played an important role in storing information. In the data file processing system, each program is designed to perform a specific purpose and has its own files without a general framework linking all the programs and possibly repeated data in more than one file. The use of these files many problems and disadvantages such as data redundancy, heterogeneity or data compatibility, limited participation, and the difficulty of maintenance. This paper introduces the overview of Database Management System (DBMS) such as its components, purposes, and data models which are describing and manipulating data, relationships between data, and constraints on the data in an organization.